Istidlal Batalnya Wudlu (Perspektif Imam Hanafi dan Imam Syafi’i) - Sutrisno Sutrisno (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2021)
This study aims to determine 1) How is Istidlal (the process of searching for and using arguments) to invalidate ablution according to Imam Hanafi and Imam Syafii and 2) What are the factors that cause the difference of opinion between Imam Hanafi and Imam Shafii regarding the cancellation of ablution. The research method used in this study is descriptive qualitative with a comparative approach that compares the opinions of two scholars about the cancellation of wudlu. The research results obtained are: 1) Istidlal: Imam Hanafi's istidlal regarding the cancellation of ablution was inspired by analogues and qiyas, because he was nicknamed "ahlu alra'yu", while Imam Shafi'i's istidlal regarding the cancellation of ablution is to look for the rules and ushul of the problem of canceling wudlu, then after finding him combine it with a valid argument or basis and this is also chosen from a valid argument. 2) Factors: The factors that cause differences of opinion between Imam Hanafi and Imam Shafi'i regarding the cancellation of ablution are the time or era factor, the scientific factor possessed, the legal basis used, the search for a legal basis in determining the law, and the experience factor.Penelitian ini bertujuan mengetahui, 1) Istidlal (proses pencarian dan penggunaan dalil) batalnya wudlu menurut Imam Hanafi dan  Imam Syafii dan 2) Faktor-faktor apakah yang menyebabkan perbadaan pendapat antara Imam Hanafi dan  Imam Syafii tentang batalnya wudlu. Adapun metode penelitian yang digunakan dalam penelitian ini adalah Kualitatif deskriptif dengan pendekatan komparatif yang membandingkan pendapat dua ulama tentang batalnya wudlu. Hasil penelitian yang diperoleh adalah1)Istidlal Imam Hanafi tentang batalnya wudlu diilhami dengan analog dan qiyas, karena beliau dijuluki ”ahlu alra’yu”,sedangkan istidlal Imam Syafi’i tentang batalnya wudlu yaitu dengan mencari kaidah-kaidah dan ushul dari permasalahan batalnya wudlu, kemudian setelah ditemukan beliau memadukan dengan dalil atau dasar yang dan ini pun dipilih dari dalil yang sahih. 2) Faktor-faktor yang menyebabkan perbedaan pendapat antara Imam Hanafi  dan Imam Syafi’i tentang batalnya wudlu adalah faktor masa atau zaman, faktor Keilmuan yang dimiliki, faktor dasar hukum yang digunakan, faktor pencarian dasar hukum dalam menetapkan hukum, dan faktor Pengalaman.